Chapter 1 (Why) do Eurosceptics believe in a common European heritage? - De Cesari, Chiara (Taylor & Francis, 2020)
This chapter reflects on the paradox of Eurosceptic populists critical of the European Union mobilizing ideas of European values, heritage, and civilization. We examine the role of the past and especially of a certain understanding of 'European heritage' in far-right-wing populist, nationalist discourse in Europe today.